The Epigenetic Impact of Vegetables-Derived Dietary Compounds in Neurodegenerative Conditions : A Review - Vania Amanda Samor; Yurida Ni'ma Annisa; Muthi Ikawati; Nunung Yuniarti (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2022)
Dietary compounds from the foods we eat on a daily basis offer several benefits; they help prevent disease and preserve health. The epigenetic advantages of the vegetables we eat every day are one of the benefits that have not been well-reported. Epigenetic pathways involving histone modification, DNA methylation, and alterations caused by miRNAs are extensively engaged in signal transmission, cell development, and death in various disease states, including brain cells. Through this narrative review collected from multiple studies available on reputable online databases until March 2022 shows the epigenetic advantages of various vegetables' content such as gallic acid, quercetin, kaempferol, apigenin, luteolin, resveratrol, genistein, sulforaphane, and diallyl disulfide in neurodegenerative conditions are summarized. However, in-depth investigations are still required to clarify these epigenetic mechanisms before these compounds are ready to be used in the future, as several studies still provide contradictory results